Schiff Base-Nickel(II) Complex: A robust luminescent probe for the detection of 2,4,6-trinitrophenol in an aqueous medium - Altun, Ayhan (Hacettepe Üniversitesi, 2025)
This study delved into the fluorescence properties of a Ni(II) Schiff base complex towards nitroaromatic compounds, such as dinitrobenzene (DNB), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (DNT), 2-nitrophenol (2-NP), 4-nitrophenol (4-NP), 2,4-dinitrophenol (DNP), and 1,3,5-trinitrophenol (TNP),. Remarkably, the compound exhibited exceptional sensitivity in detecting TNP, with a notable Ksv value of 40.5 × 103 M-1 . LOD value of the targeted compound was found to be 0.134 ?M, encompassing a linear working range of 2.50–50.00 ?M.. Furthermore, the synthesized Ni(II) complex proved effective in the fluorescence quenching-based detection of TNP in water solutions, demonstrating both high selectivity and sensitivity. Through fluorescence titrations (Job's plot), the stoichiometry between the compound and TNP was found to be 2/1 (complex/TNP). This finding underlines the potential utility of the complex as a promising tool in environmental monitoring or related fields where the detection of TNP is crucial.
Keywords: Photochemistry; Fotokimya; Physical Chemistry (Other); Fiziksel Kimya (Diğer)